2015
DOI: 10.1016/j.euroneuro.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Decreased AKT1/mTOR pathway mRNA expression in short-term bipolar disorder

Abstract: Strong evidence implicates intracellular signaling cascades dysfunction in the pathophysiology of Bipolar Disorder (BD). Regulation of AKT/mTOR pathway is a critical signaling pathway in synaptic neurotransmission and plasticity, also modulating cell proliferation and migration. Gene expression of the AKT/mTOR pathway was assessed in 25 BD (DSM-IV-TR criteria) unmedicated depressed individuals at baseline and after 6 weeks of lithium therapy and 31 matched healthy controls. Decreases in blood AKT1 and mTOR mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…For instance, a genetic variation at the AKAP13 gene, whose levels were increased by lithium in our experiment, has been previously associated with the efficacy of acute haloperidol treatment (Drago et al, 2013). Moreover, a positive correlation between AKT1 gene expression after lithium treatment and an improvement of depressive symptoms has been reported in BD patients (Machado-Vieira et al, 2015). Of note, previous findings have also linked BD with genetic variants of the AKT1 gene (Karege et al, 2012), and AKT1 expression levels have been shown to be increased in BD patients compared to controls (Gouvea et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…For instance, a genetic variation at the AKAP13 gene, whose levels were increased by lithium in our experiment, has been previously associated with the efficacy of acute haloperidol treatment (Drago et al, 2013). Moreover, a positive correlation between AKT1 gene expression after lithium treatment and an improvement of depressive symptoms has been reported in BD patients (Machado-Vieira et al, 2015). Of note, previous findings have also linked BD with genetic variants of the AKT1 gene (Karege et al, 2012), and AKT1 expression levels have been shown to be increased in BD patients compared to controls (Gouvea et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Decreased AKT1/mTOR mRNA expression has been reported in short-term bipolar disorder [48] . A recent study showed that neuronal stimulation induces NMDARdependent autophagy through the PI3K-Akt-mTOR pathway in a cellular model of LTD [25] .…”
Section: Autophagy-related Pathways In Depressionmentioning
confidence: 99%
“…Evidences also suggest Li can activate Akt, thus indirectly inhibit GSK3 [18,19,20]. Moreover, short-term bipolar disorder leads to the decrease of mRNA expression of Akt/mTOR pathway [21] and Li treatment activates mTOR in renal collecting duct cells [22]. Additionally, Li attenuates MA induced locomotor sensitization through the inhibition of GSK3β [23].…”
Section: Introductionmentioning
confidence: 96%